Activation of cellular functions in macrophages by venom secretory Asp-49 and Lys-49 phospholipases A2 - Zuliani, Juliana Pavan (2005)
The in vitro effects of myotoxin III (MT-III), an Asp-49 catalytically-active phospholipase A(2), and myotoxin II (MT-II), a catalytically-inactive Lys-49 variant, isolated from Bothrops asper snake venom, on phagocytosis and production of hydrogen peroxide (H(2)O(2)) by thioglycollate-elicited macrophages were investigated. MT-II and MT-III were cytotoxic to mouse peritoneal macrophages at concentrations higher than 25 microg/ml. At non-cytotoxic concentrations, MT-II stimulated Fcgamma, complement, mannose and beta-glucan receptors-mediated phagocytosis, whereas MT-III stimulated only the mannose and beta-glucan receptors-mediated phagocytosis. Moreover, both myotoxins induced the release of H(2)O(2) by thioglycollate-elicited macrophages, MT-III being the most potent stimulator. MT-II induced the release of H(2)O(2) only at a concentration of 3.2 microg/ml (130% increment) while MT-III induced this effect at all concentrations tested (0.5-2.5 microg/ml; average of 206% increment). It is concluded that, at non-cytotoxic concentrations, MT-II and MT-III activate defense mechanisms in macrophages up regulating phagocytosis, mainly via mannose and beta-glucan receptors, and the respiratory burst.